Who calls the tune? : a psychodramatic approach to child therapy - Hoey, Bernadette, 1934- (Routledge, 1997)
Psychodrama has its genesis in the play of children. The author explains how its powerful techniques can be safely used in working with the child who has been badly traumatized.